The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s13239-018-0344-3
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and Flow Rate Changes During Contrast Injections in Cerebral Angiography: Correlation to Reflux Length

Abstract: Cerebral angiography involves the antegrade injection of contrast media through a catheter into the vasculature to visualize the region of interest under X-ray imaging. Depending on the injection and blood flow parameters, the bolus of contrast can propagate in the upstream direction and proximal to the catheter tip, at which point contrast is said to have refluxed. In this in vitro study, we investigate the relationship of fundamental hemodynamic variables to this phenomenon. Contrast injections were carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…The power injector artifact is a larger issue that may need to be addressed by future evaluation of the injection technique and parameters. Antegrade contrast injections into the vasculature result in complex mixing phenomena at the catheter tip, and depending on the relative fluid momentums of contrast and blood, 4,5,7 injections can cause substantial hemodynamic disturbances 12 during the period of injection. Additionally, as stated above, when using a power injector, the inertia of the fluid in the large bore syringe causes contrast to emanate continually from the catheter tip, even after the injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The power injector artifact is a larger issue that may need to be addressed by future evaluation of the injection technique and parameters. Antegrade contrast injections into the vasculature result in complex mixing phenomena at the catheter tip, and depending on the relative fluid momentums of contrast and blood, 4,5,7 injections can cause substantial hemodynamic disturbances 12 during the period of injection. Additionally, as stated above, when using a power injector, the inertia of the fluid in the large bore syringe causes contrast to emanate continually from the catheter tip, even after the injection.…”
Section: Discussionmentioning
confidence: 99%
“…While the literature body is vast, functional angiography is not yet used routinely in patients because catheter-based contrast injections can cause complex and substantial hemodynamic disturbances in the vessel of interest. [4][5][6][7] However, the growth in neuro-endovascular treatment has rekindled interest in the use of angiographic techniques for flow assessment in various pathologies. [8][9][10][11][12][13][14] The treatment of aneurysms with flow diverters is particularly amenable to such analysis because (a) the reduction of intraaneurysmal flow remains a central hypothesis of treatment success; (b) flow diversion does not require (dense) intra-saccular device implantation, thus allowing for X-ray visualization of contrast transport within the aneurysm; and (c) instead of the need for extraction of absolute flow parameters, the change in intraaneurysmal contrast transport from pre-device implantation to post-device implantation can potentially be used to predict aneurysm occlusion.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction During angiography, the contrast bolus injected into a vessel can cause substantial changes in baseline pressures and flows. 1 There have been sparse case reports about aneurysmal re-bleeds during angiography. 2 A physician survey of injection rates used during angiography showed that 81% of respondents considered the impact of injection rate on aneurysm rupture to be negligible .…”
mentioning
confidence: 99%
“…Introduction Several methods of extracting arterial blood flow rates from angiography have been attempted over the past decades. 1 2 However, catheter-based contrast injections in arteries can cause substantial disturbances to the baseline blood flow, 3 which has limited the utilization of these methods in the clinical setting. Contrast reflux, which is the movement of contrast proximal to the catheter tip is frequently observed during antegrade angiography.…”
mentioning
confidence: 99%